Lichen planus and its clinical variants: a retrospective study in a tertiary care centre - Vani, Talluru; Kumar, Talamala Sampath Priya; Suma, M. (International Journal Of Community Medicine And Public Health, 2024)
Background: Lichen planus is a chronic pruritic immune-mediated disorder involving skin, oral and genital mucosa, nail and hair with several morphological variants. Although not lethal, the chronic nature of the disease have significant impact on patient’s quality of life and their psychological wellbeing. Aim was to find out clinico-epidemiological profile of LP and its variants including Dermoscopic features and its association with systemic diseases like Diabetes, Hypertension and Hypothyroidism. Methods: This is a hospital based retrospective observational study. Medical records of all patients with LP during the period from January to December 2022 were noted. Various clinico-epidemiological and dermoscopic features along with systemic disease association were analysed. Results: A total of 257 cases were reported. Most common age group affected was 41-60 yrs. Male:female ratio was 0.72:1 with female preponderance. LP in children (<18 yrs) was seen in 9.7% of cases. Classical LP was the most common type (29.5%) followed by Mucosal LP (12.45%). More than one variant was seen in 20.6% of cases. LP in association with systemic diseases was seen in 36.1% of cases with DM being the most frequent. Most common dermoscopic features were pigmentation (100%) followed by Wickham’s striae (83.6%) and vascular findings (49.4%). Conclusions: LP is a common papulosquamous disorder affecting middle aged adults with slight female preponderance. Childhood LP contributed to significant number of cases. Classical LP was the commonest clinical variant observed. LP is associated with DM, HTN and hypothyroidism. Dermoscopy is an useful tool in diagnosis and differentiating from other similar conditions.